2021
DOI: 10.1093/intqhc/mzab136
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in unmet health service needs among people with disabilities in China

Abstract: Background Extensive research has explored disparities in access to health care between people with and without disabilities, but much less is understood about disparities and associated factors within the disabled population. Objective The aim of this study was to examine differences in the prevalence of unmet health care needs by residential status (hukou status) and disability type among people with disabilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…The variable of living in rural areas has contributed to inequity for the poor. A relevant study showed that registered rural residents were related to a significant 13–40% increase in unmet health care needs for people with disabilities in China ( 50 ), and this may be attributed to the fact that people in economically disadvantaged rural areas require more health services. Therefore, the pro-poverty inequality in rural areas may also mean that individuals with more demand have received more health care.…”
Section: Discussionmentioning
confidence: 99%
“…The variable of living in rural areas has contributed to inequity for the poor. A relevant study showed that registered rural residents were related to a significant 13–40% increase in unmet health care needs for people with disabilities in China ( 50 ), and this may be attributed to the fact that people in economically disadvantaged rural areas require more health services. Therefore, the pro-poverty inequality in rural areas may also mean that individuals with more demand have received more health care.…”
Section: Discussionmentioning
confidence: 99%
“…The recognized individual needs and the assigned methods to meet them are a basis for the achievement by persons with disabilities, the aim of their active participation in social life on an equal basis with the other members of society [12]. X. Zhako and H. Wang status and the kind of disability result from many unmet needs [13].…”
Section: Description Of the State Of Knowledgementioning
confidence: 99%
“…Vulnerable people are exposed to poor environments, often have poor self-care skills, or face di culties in accessing dental care [21,22]. Access to healthcare was worse when they have physical or traveling barriers, communication di culties, and lack of nancial support [23,24]. These problems may also be due to cultural, organizational, geographical, and communication barriers, or low prioritization of dental services [25].…”
Section: Introductionmentioning
confidence: 99%